Assessing and Enhancing Nuclear Safety and Security Culture for Small Facilities that Handle Radioactive Material - Solymosi Máté (International Journal of Nuclear Security, 2017)
The use of radioactive sources is expanding all over the world and abreast the necessity of the enhancement of its safe and secure application is increasing too. In the nuclear industry, the safety and security are top priorities since decades. They share the same goal, to protect humans from the negative affect of the ionizing radiation. The human component of them is a significant factor and technical solutions can protect us so far and thus the culture for safety and security become a major focus. On the other hand, there are still some contradiction between recommendations and international guidance of the assessment of nuclear safety culture and nuclear security culture. In addition, the target audience of these guidances are the “big” users. The paper summarizes the basic knowledge about the content, the combination and the assessment of nuclear safety and security culture and offers help to the small users and facilities how to apply this toolset and enhance their own (culture for) safety and security.
Keywords: Nuclear security culture; Nuclear safety culture; Small facilities; self-assessment and enhancement